2016
DOI: 10.1007/s00438-016-1227-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci identification and meta-analysis for rice panicle-related traits

Abstract: map with 6970 markers and a total map length of 1823.1 centimorgan (cM), on which 837 QTLs were projected. These QTLs were then integrated into 87 meta-quantitative trait loci (MQTLs) by meta-analysis, and the 95 % confidence intervals (CI) of them were smaller than the mean value of the original QTLs. Also, 30 MQTLs covered 47 of the 54 QTLs detected from the cross between Nipponbare and H71D in this study. Among them, the two major and stable QTLs, spp10.1 and sd10.1, were found to be included in MQTL10.4. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 49 publications
5
58
0
Order By: Relevance
“…A meta‐analysis that could narrow down the CIs to refine and confirm the integration of QTLs by using mathematical models was widely applied in evolution and genetics researches (Goffinet & Gerber, ). Many researches have conducted the meta‐analysis method in QTL analysis, such as flowering time in maize (Chardon et al., ), panicle‐related traits in rice (Wu et al., ), fusarium head blight resistance in wheat (Liu, Hall, Griffey, & McKendry, ). However, few researches on meta‐analyses have been performed for QTL location in soybean.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis that could narrow down the CIs to refine and confirm the integration of QTLs by using mathematical models was widely applied in evolution and genetics researches (Goffinet & Gerber, ). Many researches have conducted the meta‐analysis method in QTL analysis, such as flowering time in maize (Chardon et al., ), panicle‐related traits in rice (Wu et al., ), fusarium head blight resistance in wheat (Liu, Hall, Griffey, & McKendry, ). However, few researches on meta‐analyses have been performed for QTL location in soybean.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate germplasm resources for crop utilization and improvement programs, it is essential to describe and evaluate the morphological characteristics of existing germplasm resources to effectively identify and differentiate each cultivar (Smith et al 1991;Kumbhar et al 2015;Ahmed et al 2016). The panicle traits are the most intuitive and representative rice plant part that is utilized in determining its identity and genetic diversity, as well as in estimating rice yield and quality (Chen et al 2001;Ma et al 2006;Wu et al 2016). Therefore, the characterization of rice panicle traits in relation to agricultural production and genetic diversity has long been an important research topic (Zhou et al 2003;Wang et al 2007;Zhou et al 2014;Zhao et al 2016;Adriani et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the interaction of genotype by genotype (G × G) and genotype by environment (G × E) contributed to the trait variation (Cho et al, ; Hittalmani et al, ; Zhang et al, ). Correlation analysis also revealed the strong relationship between PL and other agronomic traits, including panicle culm length, plant height, heading stage, secondary branch number and spikelet number per panicle, and these correlated traits are usually mapped synchronously (Dang et al, ; Guo & Hong, ; Huang et al, ; Jang et al, ; Liang, Shang, Lin, Lou, & Zhang, ; Lu et al, ; Miura et al, ; Sun et al, ; Wu et al, ; Yan et al, ; Zhang, Luo, Xu, Zhang, & Xing, ), Genetic dissection for rice plant architecture showed that the PL QTL is co‐localised with either culm length, tiller number or both (Kobayashi et al, ) and finely mapped with the same locus for spikelet number per panicle (Guo & Hong, ; Xie et al, ). However, whether the loci are in tight linkage or genes are in pleiotropy is unclear.…”
Section: Introductionmentioning
confidence: 99%